SMART CONTRACTS AND THE SOCIAL FUNCTION OF CONTRACTS - Knaesel Arrabal, Alejandro (2025)
The digital age has brought Smart Contracts into the environment for the use of mandatory rights, generally as an instrument of easy efficiency and a high degree of efficiency. Product of bibliographical research and discursive analysis, the article evaluates the (in)adequacy of the contractual instrument ahead of the principle of the social function of the contract. The study points to the incompatibility between Smart Contracts and the principle, given that it is an instrumental technical dimension that, in its characterization, reproduces the ideals of the legal relations of the Civil Code of 1916, extremely individualistic, a dissonant aspect compared to the Civil Code of 1916. Civil of 1916, extremely individualistic, dissonant aspect compared to the Civil Code of 1916 Civil of 2002 with the Federal Constitution of 1988, which are introduced in the alternatives a perspective and perspective for the collective and the concern for the common well-being.